Eksistensi Seni dan Ritual dalam Kehidupan Sosial Keagamaan Hindu - I Wayan Budha; Suhardi, Untung; Suarsa Putra, I Made Jaya Negara (UHN IGB Sugriwa Denpasar, 2024)
Art as part of human society can give the beauty in this life. This will then give rise to debates in Hindu religious social life that art for some people only as complementary. Alone Basic problem discussed in this paper is how do the art universally and how do relevance art and ritualistic in Hindu religious life. Methods used by qualitative analysis and theory used is dramaturgy (Goffman ) and the sacred reality (Eliade). His innovation is a man is basically it can adjust his forward with change there. Art as part of the breath of life that cannot be separated from human culture. In addition, the existence of art and ritual into something complementary because in the the gandharwa vedas also taught about the vedas is the sort of art and performances were sent to the natyasastra which in this basic emotions in art to bring up appreciation values in practice the religion.